2014
DOI: 10.1089/dia.2014.0041
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Pancreas in Healthy and Diabetic Rodent Model Using [18F]Fallypride Positron Emission Tomography/Computed Tomography

Abstract: Background: A noninvasive method of monitoring the loss of islet cells can provide an earlier and improved diagnosis for therapeutics development of preclinical phases of diabetes. The use of [18 F]fallypride, a dopamine D2/D3 receptor radiotracer, has been developed as a surrogate marker to evaluate loss of pancreatic islet cells in a rodent model of type 1 diabetes. Materials and Methods: Healthy Sprague-Dawley rats were administered [18 F]fallypride and imaged for 2 h in a positron emission tomography (PET)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…In agreement with studies suggesting the feasibility of targeting DRs for imaging BCM (15,16,19), promising results were obtained for 1 of the 3 DR radioligands. 11 C-(1)-PHNO demonstrated the greatest uptake and contrast compared with background organs in HCs.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In agreement with studies suggesting the feasibility of targeting DRs for imaging BCM (15,16,19), promising results were obtained for 1 of the 3 DR radioligands. 11 C-(1)-PHNO demonstrated the greatest uptake and contrast compared with background organs in HCs.…”
Section: Discussionsupporting
confidence: 85%
“…Using the 3 dopaminergic radioligands in our study, we can indirectly infer mechanisms of both D 2 and D 3 receptors. On the basis of preliminary success with D 2 receptor radioligands to differentiate healthy and diabetic rats (15,16), and the b-cell gene atlas data (Table 2), D 2 receptors may exist throughout the endocrine and exocrine pancreas. D 2 receptors, as measured by 11 C-(1)-PHNO, may not be directly or linearly correlated with b-cells; therefore, information obtained by this imaging technique should be viewed with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005, this hypothesis was proven when Rubi et al showed excellent co‐localization of D2 receptor expression and insulin expression in human and rodent islets . Ever since, the presence of these receptors has been exploited for imaging of insulinomas, congenital hyperinsulinism and islets, both in the pancreas and after transplantation, using [ 18 F]‐L‐3,4‐dihydroxyphenylalanine ([ 18 F]‐DOPA) and [ 18 F]fallypride Positron Emission Tomography (PET) …”
Section: Introductionmentioning
confidence: 99%
“…More recently, dopamine receptors in the pancreas have been studied as potential surrogate markers for tracking insulin-secreting islet cells in the pancreas or in transplanted islet cells (Garcia et al, 2011, 2014). The presence of D2-like receptors in the intestines has been reported to affect motility in mice (Liz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%